Structure perfection of large-size KDP crystals grown by various techniques - Puzikov, V.M.; Tkachenko, V.F.; Tsurikov, V.A. (Functional Materials, 2008)
The structure perfection of large-size KDP single crystals grown from nominally pure raw material by recirculation and solution temperature lowering techniques has been studied using the precision three-crystal X-ray diffractometry. The distribution inhomogeneity of the crystal lattice parameters Δd/d over the grown crystal volume has been established. The crystals grown by the solution recirculation technique have shown an improved structure perfection.